Gingiva-derived Mesenchymal Stem Cells and Their Potential Applications in Oral and Maxillofacial Diseases - Gao, Xudong; Cao, Zhengguo (Current Stem Cell Research & Therapy, 2020)
Background: Stem cells are undifferentiated cells with multilineage differentiation potential. They can be collected from bone marrow, fat, amniotic fluid, and teeth. Stem cell-based therapies have been widely used to treat multiple diseases, such as cardiac disease, and hematological disorders. The cells may also be beneficial for controlling the disease course and promoting tissue regeneration in oral and maxillofacial diseases. Oral-derived gingival mesenchymal stem cells are easy to access and the donor sites heal rapidly without a scar. Such characteristics demonstrate the beneficial role of GMSCs in oral and maxillofacial diseases. Objective: We summarize the features of GMSCs, including their self-renewal, multipotent differentiation, immunomodulation, and anti-inflammation properties. We also discuss their applications in oral and maxillofacial disease treatment and tissue regeneration. Conclusion: GMSCs are easily harvestable adult stem cells with outstanding proliferation, differentiation, and immunomodulation characteristics. A growing body of evidence indicates that GMSCs have strong potential use in accelerating wound healing and promoting the regeneration of bone defects, periodontium, oral neoplasms, salivary glands, peri-implantitis, and nerves. Moreover, alginate, polylactic acid and polycaprolactone can be used as biodegradable scaffolds for GMSC encapsulation. Various growth factors can be applied to the corresponding scaffolds to obtain the desired GMSC differentiation and phenotypes. Three-dimensional spheroid culture systems could optimize GMSC properties and improve the performance of the cells in tissue engineering. The immunomodulatory property of GMSCs in controlling oral and maxillofacial inflammation needs further research.
Keywords: oral